Effect of eplerenone on choroidal blood flow changes during isometric exercise in patients with chronic central serous chorioretinopathy. Issue 8 (1st March 2021) - Gallice, Mathilde; Daruich, Alejandra; Matet, Alexandre; Mouvet, Victoria; Dirani, Ali; Evequoz, Gilles; Geiser, Martial; Behar Cohen, Francine; Chiquet, Christophe
Abstract: Purpose: To investigate choroidal blood flow changes after isometric exercise in patients with chronic central serous chorioretinopathy nontreated or treated with mineralocorticoid receptor antagonists (MRA). Methods: Foveolar choroidal laser Doppler flowmetry parameters – velocity (ChVel), volume (ChVol) and blood flow (ChBF) – of 22 eyes of 22 treated patients, 16 eyes of 16 untreated patients and 19 healthy controls were measured during a squatting test. Treatment consisted in MRA administration (eplerenone 50 mg/day or spironolactone 50 mg/day). The experiment comprised three successive periods: 30 seconds of rest, 2 min of continuous squatting exercise, and 150 seconds of recovery. Significance levels were calculated using a generalized estimating equation. Results: During the squatting period, nontreated CSCR eyes had a similar change in ChVel (p = 0.8), ChVol (p = 0.8), ChBF (p = 0.5) and resistance to healthy eyes. Treated CSCR eyes exhibited significantly smaller changes in ChVel (−0.1 ± 11%, p = 0.04) than healthy eyes (6 ± 8%). No significant difference was found for ChVol and ChBF between the groups. The increase in ChVol from baseline in the nontreated CSCR group (4.4 ± 9%) was lower than that of treated group (6.7%±11%; p = 0.01). Finally, ChBF and ChVel changes in the CSCR groups were not significantly different. Conclusions: No abnormalities were detected in the changes in ChBF parameters during increased ocular perfusion pressure in nontreated CSCR patients compared with controls. MRA treatment in CSCR patients induced a significant reduction in ChBVel and an increase in ChBVol in response to isometric exercise, suggesting that MRA exerts effects on choroidal vascular changes.